The effect of hysterectomy types on vaginal length, vaginal shortening rate and FSFI scores - S. Kiremitli; T. Kiremitli; P. Ulug; N. Yilmaz; B. Yilmaz; M. Kulhan; N.G. Kulhan; K. Dinc; A. Kirkinci; F.Z. Kurnuc (Elsevier, 2022)
Objective: Vaginal length (VL), size and width may show individual differences among women. Hysterectomy causes VL shortening in patients, and this shortening varies according to the type of hysterectomy performed. Some studies in literature have shown that the shortened VL after hysterectomy may cause dyspareunia and have a negative effect on female sexuality. The aim of this study is to compare preoperative and postoperative vaginal lengths, vaginal shortening rate (VSR) not used before in the literature, and postoperative sexual functions according to hysterectomy types. Materials and methods: In the study, which included 136 [55 Total Abdominal Hysterectomy (TAH), 33 Vaginal Hysterectomy (VH), 48 Total Laparoscopic Hysterectomy (TLH)] sexually active patients under the age of 60 who underwent hysterectomy, the patients were divided into three groups according to the type of hysterectomy performed. Groups were compared in terms of demographic variables, preoperative/postop and control VL, vaginal shortening rate and The Female Sexual Function Index (FSFI) scores. Results: Vaginal lengths measured after TLH was longer and vaginal lengths measured after VAH was shorter, the difference was significant (p < 0.01). VSRs were 15.9% in TAH group, 10.9% in VH group and 8.3% in TLH group (p < 0.05). Total FSFI score was higher in TLH group than TAH and VH group (p < 0.01). Group of VSR>15% had statistically significantly lower FSFI scores in lubrication, orgasm, pain and total score than both the VSR<10% group and the VSR 10-15% group (p < 0.05). Conclusion: Calculating the VSR after hysterectomy instead of postoperative VL measurement will allow us to obtain more individual and accurate results in predicting postoperative sexual functions. We found that TLH is the best hysterectomy method in terms of preserving sexual functions due to less loss of vaginal tissue in the postoperative period from these three techniques that are frequently.